Nursing cooperation in endoscopic submucocal dissection for colorectal polyps with a diameter greater than or equal to 20mm (内镜黏膜下剥离术治疗直径大于或等于20 mm结直肠大息肉病变的护理配合) - QIN Xiaoyun (秦肖芸) (中西医结合护理)
Objective To explore the nursing cooperation skills of endoscopic submucosal dissection (ESD) in the treatment of colorectal polyps with a diameter greater than or equal to 20mm. Methods From November 2016 to December 2019 in the Department of Gastroenterology of Beijing Hospital, patients with colorectal polyps with lesion diameter ≥ 20 mm and biopsy pathology of colorectal adenoma or adenocarcinoma were selected, and the cooperation skills of nurses during operation were analyzed and summarized. Results A total of 82 patients were included in the study, and 82 lesions were collected. There were 67 cases (81. 71%) of total resection, 59 cases (71. 95%) of curative resection; 1 case (1. 22%) of delayed bleeding after operation, and 1 case (1. 22%) of postoperative delayed bleeding; 1 case (1. 22%) of mild perforation was treated with harmonious clamp, and the conservative treatment was effective. Conclusion ESD is safe and effective in the treatment of colorectal large polyps, but endoscopic nurses should make adequate preoperative preparation, intraoperative cooperation and postoperative care. The efficient and tacit cooperation of traditional Chinese medicine and nursing is very important to the success of operation, shorten the operation time and reduce the complications. (目的 探讨内镜下黏膜剥离术(ESD)治疗直径≥20 mm结直肠大息肉病变的护理配合技巧。方法 从2016年11月—2019年12月在北京医院消化内科行ESD治疗的结直肠肿瘤的患者中, 筛选出病变直径≥20 mm、活检病理为结直肠腺瘤或腺癌的患者, 对手术过程中护士的配合技巧进行分析总结。结果 共82例患者纳入研究, 收集到82处病变。其中整块切除67(81. 71%)例, 治愈性切除59(71. 95%)例; 术后迟发出血1(1. 22%)例, 再次内镜下止血处理, 痊愈出院; 术中轻度穿孔1(1. 22%)例, 使用和谐夹夹闭, 术后保守处理有效。结论 ESD治疗直径≥20 mm结直肠大息肉病变安全有效, 但需要内镜护士做好充分的术前准备、术中配合及术后护理, 术中高效默契的医护配合对手术成功、缩短手术时间及减少并发症至关重要。)